Instability of the Vertebrae Remains following Balloon Kyphoplasty. (June 2014) - Tarukado, Kiyoshi; Tono, Osamu; Ikuta, Ko; Harimaya, Katsumi; Matsumoto, Yoshihiro; Okada, Seiji; Hayashida, Mitsumasa; Iwamoto, Yukihide; Doi, Toshio
Study Design: Retrospective cohort study. Objectives: The mechanism underlying the pain relief observed following balloon kyphoplasty (BKP) to vertebral compression fractures is reported to involve stabilization of the fractured vertebrae. However, whether fixation of the vertebrae was achieved immediately after BKP has not been investigated. The purpose of this study was to assess fixation of the vertebrae immediately after BKP and whether the instability was related to visual analog scale (VAS) scores. Methods: Thirty-eight patients with vertebrae that were evaluated on lateral roentgenkymography within 1 week after BKP were recruited. Instability was defined as a cleft observed between the cement and end plate of the vertebra in the supine position that disappeared in the sitting position, and the posterior wall height of the vertebra was reduced in the sitting position. Results: Instability of the vertebrae immediately after BKP was observed in 17 cases. VAS scores improved in all cases, and no significant differences were observed with or without instability. Conclusions: The mechanism of rapid pain relief following BKP was not strong fixation but some degree of stabilization or other factors. We suggest that more research is needed about the mechanism of pain relief following BKP in the future.